ANALISIS KINERJA KEUANGAN PADA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH BINA INSAN MANDIRI GONDANGREJO PERIODE TAHUN 2016 – 2017 - Rizki Novita Iryanti; Edi Wibowo; Dorothea Ririn Indriastuti (Universitas Slamet Riyadi, 2020)
The purpose of this research is to know the level of health of the Cooperative Loan Financing and Bina Insan Mandiri Syariah Gondangrejo years of 2016 - 2017 based on the regulations Deputy Ministry Control of cooperatives and SMEs number 06/Per/Dep.6/IV/2016. This research is a case study on the Cooperative Loan Financing and Bina Insan Mandiri Syariah Gondangrejo years 2016 - 2017. The data type used is qualitative data and quantitative data. The data source in research using secondary data and primary data. Methods of data collection were used: documentation and keesioner. Data analysis techniques used to use deskripitif analysis. Based on the results of the analysis of the health assessment and loan Cooperative Bina Insan Sharia Financing and Independent Gondangrejo year 2016 obtained a score of 61.65 are on the range of values between 51 - 66, meaning categories include surveillance, while at the the year 2017 obtained a score of 66.60 are on the range of values between 66 - 80 means includes categories well enough.